Peasant Mode of Production and the Evolution of Clientelar Relations - Da Graca, Laura Cecilia (2015)
In order to characterise the relatively autonomous peasant societies that predominated in the early Middle Ages after the collapse of the state, Chris Wickham has proposed the concept of ‘peasant mode of production’. This concept refines his earlier category of ‘peasant-based society’, which the author presented as ‘deliberately anodyne’, better than the notions of ‘tribal’, ‘primitive communal’ or ‘kin-based’ societies, less naïve and restricted than that of ‘Germanic society’ inspired in Tacitus, and close to that of ‘rank society’ by reason of its distinctness from societies with class antagonism, which it shares with the former types, and its clearer recognition of internal hierarchies. This perspective has furnished a paradigm for the analysis of the early Middle Ages societies as parts of a coherent whole, which justifies a reworking of the category of peasantbased society in terms of mode of production, a task undertaken byWickham in Framing the Early Middle Ages(a peasant-based society would be a social formation dominated by the peasant mode of production). However, the author’s theoretical approach has had less of an impact than his achievements in the field of comparative studies and empirical research.